Transition of patients with Gaucher disease type 1 from pediatric to adult care: results from two international surveys of patients and health care professionals - Stepien, Karolina M.; Žnidar, Irena; Kieć-Wilk, Beata; Jones, Angel; Castillo-García, Daniela; Abdelwahab, Magy; Revel-Vilk, Shoshana; Lineham, Ella; Hughes, Derralynn; Ramaswami, Uma; Collin-Histed, Tanya (Frontiers in Pediatrics, 2024)
Gaucher disease (GD) is a rare, autosomal recessive lysosomal storage disorder caused by a deficiency in the enzyme glucocerebrosidase. The most common subtype in Europe and the USA, type 1 (GD1), is characterized by fatigue, cytopenia, splenomegaly, hepatomegaly, bone disease, and rarely pulmonary disease. Increased life expectancy brought about by improved treatments has led to new challenges for adolescents and their transition to adult care. Efficient healthcare transition to adult care is essential to manage the long-term age-related complications of the disease. This international study consisted of two online surveys: one survey for patients with GD1 and one survey for healthcare professionals (HCPs) involved in treatment of patients with GD1. The aims of this international, multi-center project were to evaluate the current transition process in various countries and to understand the challenges that both HCPs and patients experience. A total of 45 patients and 26 HCPs took part in the survey, representing 26 countries. Our data showed that a third (11/33) of patients were aware of transition clinics and most stated that the clinic involved patients with metabolic diseases or with GD. Seven patients attended a transition clinic, where most patients (5/7) received an explanation of the transition process. Approximately half of HCPs (46%; 12/26) had a transition clinic coordinator in their healthcare center, and 10 of HCPs had a transition clinic for patients with metabolic diseases in their healthcare center. HCPs reported that transition clinics were comprised of multi-disciplinary teams, with most patients over the age of 18 years old managed by hematology specialists. The main challenges of the transition process reported by HCPs included limited funding, lack of expertise and difficulty coordinating care amongst different specialties. Our study demonstrates the lack of a standardized process, the need to raise awareness of transition clinics amongst patients and the differences between the transition process in different countries. Both patients and HCPs expressed the need for a specialist individual responsible for transition, efficient coordination between pediatricians and adult specialists and for patient visits to the adult center prior to final transition of care.